Universidade e Escolas: experiências de colaboração em processos de mudança na formação dos professores - Laurizete Ferragut Passos (Universidade Estadual Paulista Júlio de Mesquita Filho, 2007)
In this work, I intend to add up some wider ideas about what i have been reflecting concerning the formacion of teachers through which I have been discussing the importance of the University researcher's role as the agent that forms and instigates the changes in the schools themselves as well as of the process of apropriation and transformation of the concepts that comprehends the teacher's practice in the classroom. Moreover, it is my intention to analyze two experiences that reveal the development of cooperation processes between University and Junior-Senior High Schools in such a way that tescher, researcher and students of the Education Course at this University perform together within a coll-formation process: from action to reflection towards formation.